ÍNDICE DE VULNERABILIDADE DAS ÁGUAS SUBTERRÂNEAS NO MUNICÍPIO DE ROSÁRIO DO SUL, RIO GRANDE DO SUL. - Ertel, Tiago; Löbler, Carlos Alberto; Silva, José Luiz Silverio da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705962 This research is part of integration award of instruments, and collection guidelines for themanagement of groundwater Project. The objective of this work was to study the groundwatervulnerability of the Rosario do Sul city, in Rio Grande do Sul state, southern Brazil on the edge ofthe Paraná Basin. It is part of the outcrops zone (ZA) Guarani Aquifer System (GAS). This aquifer isporous, unconfined, intergranular, unconfined belonging to Pirambóia Formation. Was estimatedthe aquifer pollution vulnerability index map using the GOD methodology adapted to Brazilianconditions. Were developed a database of 35 tubular wells associated with the hydrogeologicalcharacteristics of the overlying vadose zone necessary to use. Was considered groundwaterhydraulic confinement, overlying strata and the depth to groundwater table. The range of thevulnerability Index was High (40.00%), followed Moderate (28.57%), Low (14.29%), Extreme(14.29% ) and Negligible (2.85%) from the total studied area.